Modeling heart failure with preserved ejection fraction in rodents: Where do we stand? - Chou, Chun; Chin, Michael T. (Frontiers in Drug Discovery, 2022)
Heart failure (HF) with preserved ejection fraction (HFpEF) is a clinical syndrome characterized by signs and symptoms of HF in the presence of a normal left ventricular systolic function. Over the past decade, HFpEF has become increasingly prevalent, accounting for greater than 50% of all clinical HF presentations. HFpEF is a complex disease with heterogeneous clinical presentations and multiple non-cardiac comorbidities, which frequently co-exist and contribute to its pathophysiology. To date, only a handful of therapies have been proven to improve, albeit marginally, the outcomes in HFpEF. The development of effective therapeutic agents is in part hampered by the lack of animal models that adequately recapitulate human HFpEF. Although numerous pre-clinical models developed over the years have been labeled as “HFpEF” specific, there has not been a consensus on the appropriate standards for pre-clinical HFpEF models. Thus, the extent to which they truly mirror human HFpEF cannot be systematically validated. Recently, a new algorithm (H2FPEF) was developed to standardize the clinical diagnosis of HFpEF. In this review, with the aid of the clinical H2FPEF scoring system, we evaluate the clinical applicability and translational values of various murine models of HFpEF.